The Origin and Evolution of Ribonucleotide Reduction - Lundin, Daniel (Life (Basel), 2015)
Ribonucleotide reduction is the only pathway for de novo synthesis of deoxyribonucleotides in extant organisms. This chemically demanding reaction, which proceeds via a carbon-centered free radical, is catalyzed by ribonucleotide reductase (RNR). The mechanism has been deemed unlikely to be catalyzed by a ribozyme, creating an enigma regarding how the building blocks for DNA were synthesized at the transition from RNA- to DNA-encoded genomes. While it is entirely possible that a different pathway was later replaced with the modern mechanism, here we explore the evolutionary and biochemical limits for an origin of the mechanism in the RNA + protein world and suggest a model for a prototypical ribonucleotide reductase (protoRNR). From the protoRNR evolved the ancestor to modern RNRs, the urRNR, which diversified into the modern three classes. Since the initial radical generation differs between the three modern classes, it is difficult to establish how it was generated in the urRNR. Here we suggest a model that is similar to the B(12)-dependent mechanism in modern class II RNRs.